Penerapan Aplikasi Mobile untuk Pembelajaran Huruf dan Membaca pada Anak Usia Dini - Pramudika, Tuta Arya; Efendi, Dwi Marisa; Prania, Dona (MDP Student Conference, 2025)
Early childhood literacy and letter learning is an important phase in their basic literacy development. However, conventional methods are becoming less effective and less interactive as technology advances. This study aims to design and develop a mobile application as a means of interactive and interesting literacy and letter learning for early childhood by utilizing the prototyping development method. This method is implemented through several stages, namely needs analysis, prototype design, prototype evaluation, coding, system testing, user evaluation and improvements based on user feedback. In this study, a mobile application for literacy and reading learning will be created with Android Studio, and with the Kotlin programming language. The results of this study are a mobile application that functions as a tool to assist teachers and parents in the conventional teaching and learning process.